Peningkatan Kompetensi Pedagogik Guru PAI di SDN Biaro Baru Kabupaten Musi Rawas Utara - Hendri Kuswira (UIN Fatmawati Sukarno Bengkulu, 2022)
This study describes 1) the pedagogical competence of Islamic Religious Education teachers in Biaro Baru Elementary School, Karang Dapo District, Musi Rawas North Regency. 2) Analyzing the improvement of the pedagogical competence of teachers of Islamic Religious Education at Biaro Baru Elementary School, Karang Dapo District, Musi Rawas North Regency. 3) To find out the factors that become obstacles in the pedagogic development process of Islamic Religious Education teachers at the Biaro Baru Elementary School, Karang Dapo District, Musi Rawas North Regency. To explain the above, the writer uses qualitative research with a descriptive approach. From the results of the study, it is found that the pedagogical competence of Islamic Religious Education teachers at Biaro Baru Elementary School, Karang Dapo District, Musi Rawas North District is in accordance with Permendiknas No. and the Competence of Special Education Teachers, in order to increase the pedagogical competence of Islamic Religious Education teachers by including teachers in Teacher Working Group (KKG) activities, Subject Teacher Conference (MGMP) activities, then including teachers in out-of-school trainings, but there are still obstacles in the process of developing the pedagogical competence of teachers of Islamic Religious Education at the Biaro Baru Elementary School, Karang Dapo District, Musi Rawas North Regency.